Beyond KOH activation for the synthesis of superactivated carbons from hydrochar. (April 2017) - Sevilla, Marta; Ferrero, Guillermo A.; Fuertes, Antonio B.
Abstract: A novel activating agent for the production of highly microporous carbons with textural properties that match those of superactivated carbons prepared by KOH activation, i.e. BET surface areas of 2600–3000 m 2  g −1, pore volumes of ∼1.3–1.6 cm 3  g −1 and pore size distributions in the supermicropore-small mesopore (<3 nm) region, is studied. It consists of a mixture of melamine and potassium oxalate, a substance which is less corrosive than KOH, imposing less technical restrictions. Additional advantages of this activating agent are that the morphology of the particles is not altered and, importantly, the product yield is almost double that of KOH activation. The advantageous textural characteristics of the produced materials are combined with a relatively good electronic conductivity of ∼2–3 S cm −1 . When tested as supercapacitor electrodes using conventional electrolytes such as H2 SO4 and TEABF4 /AN, and less conventional ones such as EMImTFSI/AN, these carbons match the performance of benchmark KOH activated carbons and surpass that of commercial activated carbons specifically designed for supercapacitor applications. Graphical abstract: